The Association Between Childhood Trauma and Social Anxiety among Adults - Bird, Conor; Collom, Kristen; Kindscher, Jessi (Kansas State University. K-State Libraries, 2021)
The purpose of this proposal is to study the relationship between Adverse Childhood Experiences and social anxiety in adulthood. The relationship is expected to be positive, meaning that experiencing any form of childhood trauma will result in high levels of social anxiety in adulthood. Using a cross-sectional research design, 200 participants between the ages of 21 and 30 will be invited to complete a self-administered survey that will assess what specific adverse experiences in childhood correlate with social anxiety in adulthood. The independent variable, exposure to trauma, will be compared to the dependent variable, social anxiety experienced as an adult using both the Childhood Traumatic Events Scale and the Social Interaction Anxiety Scale. This research would help mental health professionals gain a better understanding of the impact of childhood trauma on social functioning, coping skills, and behavior in adulthood.
Kirmser Undergraduate Research Award - Group category, grand prize
Keywords: Adverse Childhood Experiences (ACE); Social Anxiety in Childhood; Childhood Traumatic Events Scale; Social Interaction Anxiety Scale; Adulthood; Cross-Sectional Research Design